Adipose tissue hyperplasia with enhanced adipocyte-derived stem cell activity in Tc1(C8orf4)-deleted mice - Jang, Hayoung (Sci Rep, 2016)
Adipose tissue hyperplasia with increased number of adipocytes is implicated in a protective rather than deleterious effect on obesity-associated metabolic disorder. It is poorly understood how the adipose tissue cellularity is regulated. Tc1 is a gene of vertebrates that regulates diverse downstream genes. Young Tc1-deleted mice fed on standard chow diet show expanded adipose tissue with smaller adipocytes in size compared to wild type controls, representing adipose tissue hyperplasia. Tc1(−/−) mice show enhanced glucose tolerance and reduced serum lipids. Adipocyte-derived stem cells (ADSCs) from Tc1(−/−) mice show enhanced proliferative and adipogenic capacity compared to wild type controls, suggesting that the adipose hyperplasia is regulated at the stem cell level. PPARγ and CEBPα are up-regulated robustly in Tc1(−/−) ADSCs upon induction for adipogenesis. Wisp2 and Dlk1, inhibitors of adipogenesis, are down-regulated in Tc1(−/−) ADSCs compared to controls. Tc1-transfected NIH3T3 cells show higher β-catenin reporter signals than vector transfected controls, suggesting a role of canonical Wnt signaling in the Tc1-dependent adipose regulation. Our data support that Tc1 is a novel regulator for adipose stem cells. Adipose tissue hyperplasia may be implicated in the metabolic regulation of Tc1(−/−) mice.